Retroperitoneal mature cystic teratoma in a 3-month-old infant: A case report and literature review - Prasanta Kumar Tripathy; Kaumudee Pattnaik; Pradeep Kumar Jena; Hiranya Kishore Mohanty (Indian Journal of Medical and Paediatric Oncology)
Retroperitoneal teratoma (RPT) is an exceedingly rare neoplasm in infancy. We came across a 3-month-old infant with large RPT in the left suprarenal area. The tumor was completely excised, and the patient was successfully discharged. Histopathological examination suggested the diagnosis of mature cystic teratoma.